Hybrid Transformation Model of Rural Communication Patterns in Indonesia: A Uses and Gratifications Perspective on WhatsApp Usage - Erfina Nurussa'adah; Devi Wening Astari (Ikatan Sarjana Komunikasi Indonesia, 2025)
The development of technology and information (ICT) is currently very rapid, especially with the internet network. This has various influences or impacts, both positive and negative. One of the impacts felt was the cultural transformation (pattern) of community communication in the village. The aim of the research is to describe and find a model of cultural change in interpersonal communication that occurs through social media in daily communication. The method used to realize the goal is descriptive and qualitative. Data was collected through FGDs with several informants who were selected using a purposeful technique, namely people who have a role in the environment. In addition, data was also collected through a documentation study, namely by looking at the contents of public communication messages that occur through social media, especially on WhatsApp. The research results show that the Purwobinangun community has experienced a communication transformation through the use of WhatsApp for social coordination, information dissemination, and activity reminders. This use fulfills communication needs according to the Uses and Gratifications theory, such as surveillance, correlation, entertainment, and cultural transmission. The community maintains traditional communication patterns, resulting in a hybrid communication model that combines local values and digital practices. Communication transformation creates hybrid patterns, combining social and traditional media to maintain local values and strengthen community connectedness. This model balances local cultural values with digital efficiency, enhancing social connectedness without eroding traditional cohesion. This model enhances social connectedness, mitigates exclusion, and offers empirical insights for scalable digital inclusion policies in rural contexts.